ANALISIS PROFIL KETERAMPILAN KOLABORASI MAHASISWA MENGGUNAKAN MODEL PEMBELAJARAN ENGINERING DESIGN PROCESS (EDP) - Desi Eka Nur Fitriana; Dwi Ratnasari; Mila Ermila Hendriyani (Jurnal Muara Pendidikan, 2023)
21st century skills are currently skills that are being widely developed through learning, one of which is collaboration skills. The aim of this research was to analyze the profile of students' collaboration skills through learning using the EDP model. Students were directed to overcome environmental pollution in Banten. Qualitative descriptive was a research method that used with a sample of 30 Biology Education students. The instrument used of this research was questionnaire with data collection techniques using self-assessment. There were five indicators observed, namely listening and respecting others, being flexible and compromising, working efficiently, being responsible and contributing actively. The results of the analysis show that the collaboration skills of Biology Education students with EDP learning show a very high level with an average score of 88.37.